Representación pictórica de la fiesta “KAPAK RAYMI” en la parroquia San Lucas, cantón Loja a través del expresionismo - Cueva Arrobo., Edgar Francisco (2024)
The present research titled "Pictorial Representation of the 'Kapak Raymi' Festival in the San Lucas Parish, Loja Canton through Expressionism" aims to represent the importance of this celebration and highlight its main participants through expressionist pictorial artwork. This study proposes to collect and analyze theoretical and technical postulates related to the mentioned movement, as well as to explore the customs and traditions of the Kapak Raymi festival in Saraguro culture. The research is grounded in a thorough bibliographic review and the application of deductive and inductive methods through a symbolic, iconic, and iconographic analysis of the rituals associated with Kapak Raymi. It addresses the intrinsic meaning of the most representative elements of this festival to develop artistic production, experimenting with various materials and techniques to capture the cultural essence of the celebration. The final result of the investigative process is a theoretically supported pictorial production, consisting of four artworks that visually capture the importance and cultural richness of this ancient community. These works seek to convey both the visual beauty and the intrinsic cultural meanings of the Kapak Raymi festival. Keywords: Expressionism; Kapak Raymi, Customs; Traditions; Culture; Saraguro; San Lucas.